Brainstem tuberculous abscesses successfully treated by microsurgical excision: A case report and review of the literature - Xu, Baofeng (Oncol Lett, 2017)
In patients without systemic manifestations of tuberculosis, isolated brainstem tuberculous abscesses are infrequently observed. The present study reports a rare case of two cystic tuberculous abscesses involving the dorsal aspect of the medulla oblongata in an otherwise healthy 14-year-old Chinese girl, whose primary complaint was respiratory distress. These lesions were successfully treated using a microsurgical excision approach and anti-tuberculosis therapy. Although rare, tuberculous abscesses should be considered in the differential diagnosis of isolated cystic brainstem lesions. The results of the present study indicate that microsurgery, when combined with anti-tuberculosis therapy, is an effective and safe method to treat brainstem tuberculous abscesses.